Characterization of Dental Surgeons of Pernambuco State in the COVID-19 Pandemic Context: Preliminary Data - Gabriela da Silveira Gaspar; Nilcema Figueiredo; Edson Hilan Gomes de Lucena; Cindy Avani Silva Ceissler; Ronald Pereira Cavalcanti; Paulo Sávio Angeiras de Goes (Association of Support to Oral Health Research (APESB), 2022)
Objective: To present the results of preliminary research on the characterization of dental surgeons in the state of Pernambuco, during a pandemic of COVID-19. Material and Methods: This is a cross-sectional, descriptive, and exploratory study, whose population was composed of dental surgeons with active enrollment in the Regional Dentistry Council of Pernambuco. Data collection was performed using an electronic form and included characterization of professionals (gender, age, time since graduation, marital status, family income and field of work) and health status (vaccination schedule, presence of comorbidities, biosafety knowledge and testing for COVID-19). Preliminary data correspond to the first week of collection, which were analyzed from the frequency, proportions, and measures of central tendency distributions. Results: Of the 363 dental surgeons, for the field of work, 38.6% work in both the public and private sectors. Comorbidities related to the worsening of COVID-19 were identified in 35.0% of participants, 24.5% are not up to date with influenza and hepatitis vaccines, and 79.3% have not been tested for COVID-19. Regarding the biosafety instructions for COVID-19, 30.7% received no training. Conclusion: It is necessary to immunize dental surgeons to prevent immunological diseases and expansion of the testing capacity for COVID-19, especially for professionals belonging to the risk group. In addition to guaranteeing the offer of qualification courses on biosafety, which is essential for the safe resumption of activities.